The Effect of Sales Growth, Leverage, and Profitability on Company Value with Tax Avoidance as an Intervening Variable - Rejeki, Ires Azri; Fahmi, Muhammad; Yunita, Khristina; Dosinta, Nina Febriana (Sebatik, 2025)
This study aims to determine the effect of Sales Growth, Leverage, and Profitability on Company Value with Tax Avoidance as an Intervening Variable. This study is based on the Sales Growth Ratio, with the indicator being the Net Sales Growth Ratio, Leverage with the indicator being the Debt-to-Equity Ratio (DER), Profitability with the indicator being Return on Equity (ROE), and Tax Avoidance with the indicator being the Effective Tax Rate (ETR). The method used is quantitative with a focus on numerical data. The data used is secondary data obtained from the annual reports of companies classified in the retail sector listed on the Indonesia Stock Exchange (IDX) during the period 2021 to 2024. The sampling technique used purposive sampling, with a sample size of 15 companies and 60 observations. The analysis method used is panel data regression, which is a combination of time series data and cross-sectional data. An intervening test was also conducted to determine the role of tax avoidance in strengthening or weakening the relationship between sales growth, leverage, and profitability on company value. All data processing was performed using EViews software. The results of the study indicate that Sales Growth, leverage, and profitability as independent variables, as well as Tax Avoidance as an intervening variable, do not have a significant effect on company value. Furthermore, Sales Growth, leverage, and profitability with Tax Avoidance as an intervening variable also do not have a significant effect on company value.